FGF19 regulates cell proliferation, glucose and bile acid metabolism via FGFR4-dependent and independent pathways. - Ai-Luen Wu; Sally Coulter; Christopher Liddle; Anne Wong; Jeffrey Eastham-Anderson; Dorothy M French; Andrew S Peterson; Junichiro Sonoda (PLoS ONE, 2011)
Fibroblast growth factor 19 (FGF19) is a hormone-like protein that regulates carbohydrate, lipid and bile acid metabolism. At supra-physiological doses, FGF19 also increases hepatocyte proliferation and induces hepatocellular carcinogenesis in mice. Much of FGF19 activity is attributed to the activation of the liver enriched FGF Receptor 4 (FGFR4), although FGF19 can activate other FGFRs in vitro in the presence of the coreceptor βKlotho (KLB). In this report, we investigate the role of FGFR4 in mediating FGF19 activity by using Fgfr4 deficient mice as well as a variant of FGF19 protein (FGF19v) which is specifically impaired in activating FGFR4. Our results demonstrate that FGFR4 activation mediates the induction of hepatocyte proliferation and the suppression of bile acid biosynthesis by FGF19, but is not essential for FGF19 to improve glucose and lipid metabolism in high fat diet fed mice as well as in leptin-deficient ob/ob mice. Thus, FGF19 acts through multiple receptor pathways to elicit pleiotropic effects in regulating nutrient metabolism and cell proliferation.